The effect of S doping on the superconductivity and nematicity transition of FeSe. (February 2020) - Ma, Qingshuang; Lan, Feng; Li, Xinhua; Du, Zunfeng; Li, Huijun; Ma, Zongqing
Abstract: In this work, the superconducting properties of FeSe1−x Sx with 0 ≤  x  ≤ 0.5 were studied. With S doping, T c is enhanced and shows a dome shape in the studied composition range. XRD measurements demonstrate that S substituting Se sites introduces positive chemical pressure, which can suppress the orbital ordering, manifesting as the decrease of T s . Hall measurements demonstrate that S doping can effectively tune the charge carriers and make hole-type carriers predominant. However, no maxing T c is obtained as T s vanishes in FeSe0.7 S0.3, indicating the nematic order has no universal influence on the superconductivity of FeSe system. Graphical abstract: Image, graphical abstract